Jejak Bencana Alam di Kerinci dan Dampaknya Bagi Masyarakat dan Pemerintah Kolonial Belanda 1920-1939 - Darmawan, Budi; Puji Azizah, Faras; Alhuzaini, Muhammad (Siginjai: Jurnal Sejarah, 2023)
This article discusses the natural disasters that occurred in Kerinci during the Dutch colonial period 1920-1939. In this disaster the people of Kerinci suffered enormous losses. For this reason, in the study there are several problems to be discussed, namely, what natural disasters hit Kerinci during the Dutch Colonial period. The historical method used in this research is by collecting data through heuristics, source criticism, interpretation, and historiography. The results of this study reveal that Kerinci experienced a series of natural disasters in 1920-1939. Earthquakes, floods, fires, and others. Some events such as earthquakes were not considered destructive, and there were also events that caused material losses and casualties. Kerinci's geography is often a factor in triggering natural disasters to occur. In 1939, an earthquake that shook Kerinci served as a reminder of the potential dangers inherent in its natural beauty, especially the presence of the active Mount Kerinci. Although the community showed resilience and solidarity, disaster management during the colonial period was centered on the government, which undertook mitigation efforts and coordinated relief such as the delivery of medicines and medical and other assistance. This research provides an overview of Kerinci's vulnerability to natural disasters during the Dutch colonial period. While communities and the colonial government attempted to respond to disasters, challenges and complexities remained part of the relief effort.